The Synthesis of Novel 7-(Substituted benzyl)-4,5-dihydro[1,2,3]triazolo[1,5-a]pyrazin-6(7H)-ones via Tandem Ugi–Huisgen Reactions - Pokhodylo, Nazariy T.; Тupychak, Mykola A.; Goreshnik, Evgeny A.; Obushak, Mykola D. (Synthesis, 2022)
A convenient method for the synthesis of 2-azido-3-arylpropanoic acids via the Meerwein halogenoarylation reaction of acrylic acid esters with diazonium salts, subsequent nucleophilic substitution of the halogen by an azide, and saponification is developed. The newly formed 2-azido-3-arylpropanoic acids react under the conditions of non-catalytic four-component Ugi reactions, leading to the formation of α-azidoamides in good yields. The use of propargylamine as the amine component allows the formation of Ugi adducts with azide and acetylene motifs ready for intramolecular 1,3-dipolar Huisgen cycloaddition to give the [1,2,3]triazolo[1,5-a]pyrazine annulated system. The Ugi reaction is found to give 2-azido-3-aryl-N-(2-oxo-1,2-disubstituted ethyl)-N-(prop-2-yn-1-yl)propanamides at room temperature without azide–alkyne cycloaddition. These dipeptides are converted into 4,5-dihydro[1,2,3]triazolo[1,5-a]pyrazin-6(7H)-ones in near quantitative yields by heating in toluene. However, when the Ugi reaction is carried out by heating, it results in a one-pot Ugi–Huisgen tandem reaction leading to 4,5-dihydro[1,2,3]triazolo[1,5-a]pyrazin-6(7H)-ones in excellent yields. Moreover, the possibility of the incorporation of a bromovinyl fragment (the synthetic equivalent of an acetylene fragment) via the aldehyde component of the Ugi reaction is demonstrated in an alternative preparation of the [1,2,3]triazolo[1,5-a]pyrazine system.
Keywords: azides; 1,2,3-triazoles; [1,2,3]triazolo[1,5-a]pyrazines; Ugi reaction; Huisgen cycloaddition; one-pot; Meerwein reaction